Memory and tradition in Israel - Childs, Brevard Springs, 1923- (Naperville, IL Alec R. Allenson, 1962)
Includes bibliographical references and indexes.
Donated from the library of Mr John Fraser Dickson, November, 2002.
Keywords: Bible. O.T. -- theology